Effect of the inertia variation on crankshaft vibration - Lim, Bo Xiong. (2013)
Crankshaft vibration problem is always a major concern in the design of an internal combustion engine. Studies focusing on this problem have been carried out intensively over the past years. With the improvement on the engine, engine speed and gas pressures have increased. The engine crankshaft experiences greater and more serious vibrations. As most researches were done on pure torsional and bending vibration problem, this report aims to provide an insight to the coupled torsional-bending vibrations analysis.